Thermoelasticity of Fe7C3 under inner core conditions. Issue 8 (4th August 2016) - Li, Y.; Vočadlo, L.; Brodholt, J.; Wood, I. G.
Abstract: It has recently been reported, on the basis of extrapolated experimental data, that the iron carbide, Fe7 C3, has shear wave velocities and a Poisson's ratio consistent with the seismological values for the Earth's inner core and thus that Fe7 C3 is a strong candidate for the inner core composition. In this study, using ab initio molecular dynamics simulations, we report the thermoelastic properties of Fe7 C3 at 350 GPa up to its melting temperature. Due to significant elastic softening prior to melting, the calculated elastic properties, including wave velocities, do indeed agree well with those from seismology. However, the density was found to be much too low (by 8%) when compared to geophysical data, and therefore, Fe7 C3 must be ruled out as a major component of the Earth's inner core. Key Points: The thermoelasticity of Fe7 C3 was calculated using AIMD under the Earth's inner core conditions The elastic properties of Fe7 C3 agree well with those from seismology due to significant premelting effects Fe7 C3 cannot be the major component of the Earth's core due to its low density